Evaluasi Uraian Tugas Di Sub Bagian Rekam Medis Dan Sistem Informasi Manajemen BLUD RSUD DATU SANGGUL RANTAU - Sabar Kristina; Dimas Eka Saputra; Eva Khairita; STIKES Husada Borneo; Alumni STIKES Husada Borneo (HB PRESS, 2016)
Introduction: In healthcare or hospital that became the main pillar in the smooth implementation is the medical record. To carry out the necessary work in the medical record that meets the human resource competency based on job descriptions that exist in the medical record unit. Problem in the research is a job description in the medical record unit is still not effective and execution of the job descriptions is less than optimal because the job description is designed not clearly defined and directed. Evaluation study aims to determine the job description in sub section medical records and information management system BLUD RSUD Datu Sanggul Rantau. Method: This research is descriptive method of research subjects using a computerized system analysis unit and job description. Data collection techniques in this study by interview and observation, with the presentation of the data in the form of tekstular. Result: The results showed that there was a good job descriptions job descriptions in the evaluation of qualifications, but the job descriptions can not be understood by some staff due to inaccurate medical records job description that is not spelled out in detail the main tasks so that sometimes there are those who do not understand the task should be done and execution of the job description is still not appropriate to the task at work unit medical record. Conclusion: Discussion of this research is to facilitate making job descriptions need to know what activities are supposed to exist in the medical records, and job descriptions are designed properly and must meet the qualification assessment of job descriptions for the implementation of the tasks carried out in accordance with the existing job descriptions.